Hormone Replacement Therapy in a Patient with Hypogonadism and Coexisting Medical Conditions - Özlem Dural; Şükran Poyrazoğlu (JCRPE, 2020)

(untitled)
In adolescents and young women, there is limited data on the type of replacement, route of administration, and ideal doses to be used in systemic hormone therapy administered for the treatment of hypogonadism. In particular, management of patients with complicated systemic diseases or at risk of thrombophilia may present significant challenges. We present a case of a 15-year-old adolescent girl with hypogonadism and coexisting medical conditions, who was evaluated for systemic hormone therapy.